Moringa oleifera seed meal as a sustainable fishmeal substitute: Growth and health implications for Cirrhinus mrigala - Sadia Tabassum; Syed Makhdoom Hussain; Shafaqat Ali; Pallab K. Sarker; Khalid A. Al-Ghanim; Lalarukh (Aquaculture Reports)
As global protein demands rise, fish protein has become an essential component of food security. However, the scarcity of fishmeal necessitates the development of sustainable aquaculture solutions utilizing affordable plant-based alternatives. This study explores the impact of replacing fishmeal with varying levels of Moringa oleifera seed meal (MOSM) such as 0 %, 10 %, 20 %, 30 %, 40 %, and 50 %, on the growth, hematological indices, carcass composition, nutrient digestibility, and mineral status of Cirrhinus mrigala (6.75 ± 0.03 g/fish). In a 90-day feeding study, 270 fingerlings were randomly assigned to six groups, each receiving one of six diets with varying MOSM concentrations. Each group consisted of three replicate tanks, with 15 fingerlings per tank. The results demonstrated significant (P<0.05) improvements in specific growth rate, feed conversion ratio, and weight gain percentage with 10 % MOSM substitution of fishmeal. Proximate body composition revealed optimal crude protein (74 %), crude fat (81 %), and gross energy (61 %) levels in fish fed the 10 % MOSM diet. Hematological evaluations showed favorable profiles, with lower MCH and MCV levels, and increased RBCs, WBCs, Hb, and MCHC. The nutrient and mineral digestibility analysis revealed that 10 % MOSM was the optimal replacement level for fish meal. In contrast, 50 % MOSM substitution resulted in decreased growth performance, carcass quality, mineral status, nutrient digestibility and hematological parameters. Replacing 10 % of fishmeal with MOSM offers a viable economic solution for aquaculture, enhancing growth, hematological parameters, nutrient digestibility, carcass quality, and mineral status in C. mrigala fingerlings.